Pemikiran Al-ghazali Tentang Tasawuf dalam Pembentukan Karakter Generasi Milenial - Ade Yanti; Devi Idhah Nursyafitri; Desy Rahmalia; Ismail Mubarok (Jurnal Insan Pendidikan dan Sosial Humaniora, 2026)
The development of technology and the flow of globalization in the digital era have brought various challenges for the millennial generation, especially related to moral and spiritual crises and declining character quality. This study aims to analyze the concept of Sufism according to Imam Al-Ghazali and its relevance in shaping the character of the millennial generation. The method used is library research with a qualitative approach through a study of Al-Ghazali's works and various relevant supporting literature. The results of the study indicate that Al-Ghazali's concept of Sufism, which is based on tazkiyatun nafs (purification of the soul), riyadhah (spiritual practice), and spiritual stages (maqamat) such as repentance, patience, gratitude, asceticism, and mahabbah, plays an important role in shaping a character with noble morals. These values ​​can help the millennial generation control themselves, increase self-awareness, strengthen spiritual intelligence, and ward off the negative influences of materialism, hedonism, and excessive digital culture. Thus, Al-Ghazali's Sufi thought is relevant to be applied in education and daily life as an effort to form a generation that is intellectually superior, emotionally mature, and strong in moral and spiritual values.